Expression of cannabinoid (CB1 and CB2) and cannabinoid-related receptors (TRPV1, GPR55, and PPARα) in the synovial membrane of the horse metacarpophalangeal joint - Zamith Cunha, Rodrigo; Zannoni, Augusta; Salamanca, Giulia; De Silva, Margherita; Rinnovati, Riccardo; Gramenzi, Alessandro; Forni, Monica; Chiocchetti, Roberto (Frontiers in Veterinary Science, 2023)
Background: The metacarpophalangeal joint undergoes enormous loading during locomotion and can therefore often become inflamed, potentially resulting in osteoarthritis (OA). There are studies indicating that the endocannabinoid system (ECS) modulates synovium homeostasis, and could be a promising target for OA therapy. Some cannabinoid receptors, which modulate proliferative and secretory responses in joint inflammation, have been functionally identified in human and animal synovial cells. Objective: To characterise the cellular distribution of the cannabinoid receptors 1 (CB1R) and 2 (CB2R), and the cannabinoid-related receptors transient receptor potential vanilloid type 1 (TRPV1), G protein-related receptor 55 (GPR55) and peroxisome proliferator-activated receptor alpha (PPARα) in the synovial membrane of the metacarpophalangeal joint of the horse. Animals: The dorsal synovial membranes of fourteen equine metacarpophalangeal joints were collected post-mortem from an abattoir. Materials and Methods: The dorsal synovial membranes of fourteen equine metacarpophalangeal joints were collected post-mortem from an abattoir. The expression of the CB1R, CB2R, TRPV1, GPR55 and PPARα in synovial tissues was studied using qualitative and quantitative immunofluorescence, and quantitative real-time reverse transcriptase PCR (qRT-PCR). Macrophage-like (MLS) and fibroblast-like (FLS) synoviocytes were identified by means of antibodies directed against IBA1 and vimentin, respectively. Results: Both the mRNA and protein expression of the CB2R, TRPV1, GPR55 and PPARα were found in the synoviocytes and blood vessels of the metacarpophalangeal joints. The synoviocytes expressed the mRNA and protein of the CB1R in some of the horses investigated, but not in all. Conclusions and clinical importance: Given the expression of the CB1R, CB2R, TRPV1, GPR55 and PPARα in the synovial elements of the metacarpophalangeal joint, these findings encouraged the development of new studies supporting the use of molecules acting on these receptors to reduce the inflammation during joint inflammation in the horse.